2016
DOI: 10.1152/ajpregu.00367.2015
|View full text |Cite
|
Sign up to set email alerts
|

The role of cerebral oxygenation and regional cerebral blood flow on tolerance to central hypovolemia

Abstract: Kay VL, Rickards CA. The role of cerebral oxygenation and regional cerebral blood flow on tolerance to central hypovolemia. Am J Physiol Regul Integr Comp Physiol 310: R375-R383, 2016. First published December 16, 2015 doi:10.1152/ajpregu.00367.2015Tolerance to central hypovolemia is highly variable, and accumulating evidence suggests that protection of anterior cerebral blood flow (CBF) is not an underlying mechanism. We hypothesized that individuals with high tolerance to central hypovolemia would exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…In healthy adult volunteers, cerebral oxygenation measured by NIRS during hypovolemia has been studied experimentally by applying lower body negative pressure. 30,31 Literature on the effects of hypotension on NIRS oximetry measures in neonatal populations is limited. In preterm infants, mild short-term hypotensive episodes did not lower the cerebral oxygenation estimated by NIRS.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adult volunteers, cerebral oxygenation measured by NIRS during hypovolemia has been studied experimentally by applying lower body negative pressure. 30,31 Literature on the effects of hypotension on NIRS oximetry measures in neonatal populations is limited. In preterm infants, mild short-term hypotensive episodes did not lower the cerebral oxygenation estimated by NIRS.…”
Section: Discussionmentioning
confidence: 99%
“…9 Cerebral perfusion associated with high and low tolerance to hemorrhage An individual's tolerance to central hypovolemia during LBNP (simulated blood loss) largely reflects a reached ''threshold'' during a progressive reduction in cerebral blood flow and oxygenation. 10 A tracing of a continuous transcranial Doppler (TCD) measurement obtained from a Schiller et al The physiology of blood loss and shock 875 human subject undergoing progressive LBNP is presented in Figure 3(a). The TCD provides a measure of mean cerebral artery velocity (MCAv) which is progressively reduced as the subject's central blood volume decreases.…”
Section: Comparison Of Lbnp and Actual Hemorrhagementioning
confidence: 99%
“…Both blood loss and LBNP elicit similar responses in key haemodynamic parameters, including heart rate, stroke volume, cardiac output, arterial pressure and cerebral blood velocity (Hinojosa-Laborde et al, 2014;Johnson et al, 2014;. In studies using maximal LBNP to presyncope, it has been demonstrated that there is a continuum of tolerance among healthy human subjects (Kay & Rickards, 2016;Levine, Giller, Lane, Buckey, & Blomqvist, 1994;Lightfoot & Tsintgiras, 1995;Rickards, Ryan, Cooke, & Convertino, 2011), which has been attributed, in part, to protection of absolute blood flow (Levine et al, 1994;Lieshout, Wieling, Karemaker, & Secher, 2003) in either the anterior (Levine et al, 1994;Rickards et al, 2011) or the posterior circulation (Kay & Rickards, 2016) of the brain. In studies using maximal LBNP to presyncope, it has been demonstrated that there is a continuum of tolerance among healthy human subjects (Kay & Rickards, 2016;Levine, Giller, Lane, Buckey, & Blomqvist, 1994;Lightfoot & Tsintgiras, 1995;Rickards, Ryan, Cooke, & Convertino, 2011), which has been attributed, in part, to protection of absolute blood flow (Levine et al, 1994;Lieshout, Wieling, Karemaker, & Secher, 2003) in either the anterior (Levine et al, 1994;Rickards et al, 2011) or the posterior circulation (Kay & Rickards, 2016) of the brain.…”
Section: Introductionmentioning
confidence: 99%